A retrospective critic Re-Debate on Stakeholders' resistance checklist in software project management within multi-cultural, multi-ethnical and cosmopolitan society context: The Malaysian experience - Hamed Taherdoost; Abolfazl Keshavarzsaleh; Chen Wang (Cogent Business & Management, 2016)
Risks stemming from software projects were extensively studied. However, software project risk management has rarely researched organizational risks within multi-cultural and multi-ethnical atmospheres. The fact of the matter is that problems occur when the stakeholders' cultural and ethnical aspects are not addressed, especially in multi-cultural, multi-ethnical, and cosmopolitan society such as Malaysia. To avoid analyzing something that has already been studied in detail, this study conducted based on in-depth literature review considering key word search in subject-specific databases. Journal articles published in reputed journals were reviewed. By employing Rumelt's resistance to change checklist and culture gap tool source, this paper develops an organizational risk framework considering cross-cultural and cross-ethnical critical factors in order to show how can risks be better comprehended and managed. The significance of bio-cultural dimensions was scrutinized as vital criteria which should be considered in international project sphere, so that, not only the odds of project success would be increased but also the risks can be mitigated significantly. A review of the risk management process, Rumelt's Checklist, cultural issues in international project environment allows a better understanding of the importance of cultural dimensions in project spheres.
Keywords: 650